Millennial-scale vegetation dynamics in an estuary at the onset of the Miocene Climate Optimum - Kern, Andrea (2011)
Pollen analyses have been proven to possess the possibility to decipher rapid vegetational and climate shifts in Neogene sedimentary records. Herein, a c. 21-kyr-long transgression–regression cycle from the Lower Austrian locality Stetten is analysed in detail to evaluate climatic benchmarks for the early phase of the Middle Miocene Climate Optimum and to estimate the pace of environmental change. Based on the Coexistence Approach, a very clear signal of seasonality can be reconstructed. A warm and wet summer season with c. 204–236 mm precipitation during the wettest month was opposed by a rather dry winter season with precipitation of c. 9–24 mm during the driest month. The mean annual temperature ranged between 15.7 and 20.8 °C, with about 9.6–13.3 °C during the cold season and 24.7–27.9 °C during the warmest month. In contrast, today’s climate of this area, with an annual temperature of 9.8 °C and 660 mm rainfall, is characterized by the winter season (mean temperature: −1.4 °C, mean precipitation: 39 mm) and a summer mean temperature of 19.9 °C (mean precipitation: 84 mm). Different modes of environmental shifts shaped the composition of the vegetation. Within few millennia, marshes and salt marshes with abundant Cyperaceae rapidly graded into Taxodiaceae swamps. This quick but gradual process was interrupted by swift marine ingressions which took place on a decadal to centennial scale. The transgression is accompanied by blooms of dinoflagellates and of the green alga Prasinophyta and an increase in Abies and Picea. Afterwards, the retreat of the sea and the progradation of estuarine and wetland settings were a gradual progress again. Despite a clear sedimentological cyclicity, which is related to the 21-kyr precessional forcing, the climate data show little variation. This missing pattern might be due to the buffering of the precessional-related climate signal by the subtropical vegetation. Another explanation could be the method-inherent broad range of climate-parameter estimates that could cover small scale climatic changes.